Clinical Safety and Effectiveness of Collagenase Clostridium Histolyticum Injection in Patients with Peyronie's Disease: A Phase 3 Open‐Label Study. (12th November 2014) - Levine, Laurence A.; Cuzin, Beatrice; Mark, Stephen; Gelbard, Martin K.; Jones, Nigel A.; Liu, Genzhou; Kaufman, Gregory J.; Tursi, James P.; Ralph, David J.
Abstract Introduction Collagenase clostridium histolyticum (CCH; Xiaflex, Auxilium Pharmaceuticals, Inc., Chesterbrook, PA, USA) is a Food and Drug Administration‐approved, intralesional treatment for Peyronie's disease (PD). Aim The aim of this study was to assess the safety and effectiveness of CCH in the treatment of PD. Methods This phase 3, open‐label study enrolled subjects who were CCH‐naïve, were enrolled in a previous pharmacokinetic study, or had received placebo in an earlier phase 2 CCH study. Each treatment cycle included two intralesional injections of CCH 0.58 mg, approximately 24–72 hours apart, and plaque modeling 24–72 hours after the second injection of each cycle. The treatment cycle was repeated after 6 weeks for ≤4 treatment cycles. Main Outcome Measures The co‐primary end points were the mean percent change in penile curvature deformity and the mean improvement in PD bother score (range 0–16) from baseline to week 36. Results Of the 347 subjects treated with ≥1 injection, 238 had both a penile curvature measurement and a Peyronie's Disease Questionnaire response at baseline and ≥1 subsequent time point. Mean baseline penile curvature deformity was 53.0° and mean PD symptom bother was 7.3. Statistically significant mean improvements from baseline to week 36 were observed in both penile curvature deformity (34.4% [95% confidence interval CI, 31.2%, 37.6%]) and PD symptom bother score (3.3 [95% CI, 2.8, 3.7]). Most adverse events (AEs) were mild or moderate in severity and local to the penis. There were three serious treatment‐related AEs, two penile hematomas and one corporal rupture; all resolved with treatment. Conclusions Potentially clinically meaningful and statistically significant improvements in penile curvature deformity and PD symptom bother scores were observed with intralesional injection of CCH compared with baseline in men with PD. CCH was generally well tolerated, with AEs primarily transient and local to injection site. In conjunction with previous studies, the results of this open‐label study support the use of CCH in the treatment of PD. Levine LA, Cuzin B, Mark S, Gelbard MK, Jones NA, Liu G, Kaufman GJ, Tursi JP, and Ralph DJ. Clinical safety and effectiveness of collagenase clostridium histolyticum injection in patients with Peyronie's disease: A phase 3 open‐label study. J Sex Med 2015;12:248–258.